Influência da potência do motor do grupo gerador na limitação de produção de energia elétrica de um sistema formado por um gaseificador/grupo gerador - Melo, Vinicius Mafra (2018)
Throughout the modern era, humanity has been using fossil fuels to meet their needs. Coal, oil and natural gas have contributed to the lighting and functioning of machines, promoting the quality of life. The continued use of these resources has, however, evidenced their limited availability. At the same time, these sources greatly pollute the environment, stimulating the search for more ecological resources. Among the main non-fossil fuels, biomass, in Brazil has been gaining prominence due to the large reserves available and its natural calling for biofuels. Biomass gasification provides a mean of deriving more diverse forms of energy from thermochemical conversion, representing an efficient process for the production of energy and heat. In order to improve the productivity of biomass gasifiers, the present work examines whether the limitation of the electric energy production of a system formed by a biomass gasifier and a generator set can be determined by the choice of generator set engine. The gasifier in question is a fixed-bed, co-current, open top type, imported from the Indian of Science / Combustion Gas Propulsion Laboratory, IISc / CGPL, with a thermal capacity of 80 kWt, which has been adapted to serve to gas engines. In order to consolidate the objectives, the generator set was replaced by a MWM 229-4 engine and a 36 kVA generator, to other consisting of the MWM 229-6 engine and a 150 kVA generator. In both cases the diesel engines were converted to otto cycle and set to work with poor gas, operating with a commanded ignition system. The tests were carried out at the Laboratory of Innovation in Thermal Conversion of the Federal University of Paraíba-UFPB and verified that the use of a generator group with greater capacity allowed the previously generated power of 29 kW to pass to 32 kW, although the average thermal efficiency of the system, the highest power is from 98% to 93.65%.